2010
DOI: 10.4014/jmb.0911.11020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dissolved Oxygen on Fungal Morphology and Process Rheology During Fed-Batch Processing of Ganoderma lucidum

Abstract: Controlling the dissolved oxygen (DO) in the fed-batch culture of the medicinal mushroom Ganoderma lucidum led to a 2-fold increase of the maximum biomass productivity compared with uncontrolled DO conditions. By contrast, extracellular polysaccharide (EPS) production was two times higher under oxygen limitation (uncontrolled DO) than under increased oxygen availability (controlled DO). Morphologically, dispersed mycelium was predominant under controlled DO conditions, with highly branched hyphae, consistent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 29 publications
(34 reference statements)
1
25
1
Order By: Relevance
“…Lee et al (2004) and Park et al (1999) revealed that ''feather-like'' morphology was more favorable than pellets in the production of extracellular polysaccharide and arachidonic acid from Grifola frondosa and Mortierella alpina, respectively. In another report, it was pointed out that more dispersed mycelia observed under controlled dissolved oxygen (DO) conditions were associated with better growth, whereas the predominant clumps present in the uncontrolled DO culture led to more than 2 times higher extracellular polysaccharide productivity (Fazenda et al 2010). In contrast to the present study, it was observed that degradation and decolorization of the spent wash were high when the pellet formation exists in rigid condition than it was in fragment and mycelia form.…”
Section: Resultscontrasting
confidence: 55%
“…Lee et al (2004) and Park et al (1999) revealed that ''feather-like'' morphology was more favorable than pellets in the production of extracellular polysaccharide and arachidonic acid from Grifola frondosa and Mortierella alpina, respectively. In another report, it was pointed out that more dispersed mycelia observed under controlled dissolved oxygen (DO) conditions were associated with better growth, whereas the predominant clumps present in the uncontrolled DO culture led to more than 2 times higher extracellular polysaccharide productivity (Fazenda et al 2010). In contrast to the present study, it was observed that degradation and decolorization of the spent wash were high when the pellet formation exists in rigid condition than it was in fragment and mycelia form.…”
Section: Resultscontrasting
confidence: 55%
“…Working on Ganoderma lucidum in submerged culture in shaken flasks on a medium containing peptone, yeast extract, and glucose, Wagner et al (2004) concluded that manipulating the physiological events and subsequent morphological characteristics of pellets during the culture of G. lucidum will allow the proposal of culture strategies to improve exopolysaccharide production. However, Fazenda et al (2010) concluded that fungal morphology and broth rheology influenced the extracellular polysaccharide, wherein the clump form was the most productive morphology in terms of EPS production, compared with the free filamentous mycelial form. Investigating the morphological and rheological properties in submerged culture of three different species of the basidiomycete Phellinus (P. baumii, P. gilvus, and P. linteus), Hwang et al (2004) reported that morphological change in the pellets of the three species of Phellinus was a good indicator for identifying cell activity for pharmacologically important exopolysaccharide production.…”
Section: Effects Of Different Agitation Rates On Development Of Mycelmentioning
confidence: 96%
“…Fazenda et al. reported Newtonian behavior for an EPS containing filtrate of G. lucidum with a constant viscosity of 9 mPa.s at 30°C, whereas the culture broth before cell separation showed shear‐thinning behavior. On the other hand, Aouadi et al.…”
Section: Analysis and Application Of Exopolysaccharidesmentioning
confidence: 99%
“…Cho et al [91] observed proportionality between fermentation broth viscosity and cell density during cultivation of Paecilomyces sinclairii whereas, after using cultures of P. florida, Burns et al [92] related the viscosity increase mainly to water-soluble extracellular compounds. As regards cell morphology, filamentous growth and the corresponding spatial cross-linked distribution of the hyphae caused more pronounced effects on fermentation broth rheology, namely presence of a yield stress and shear-thinning flow behavior [29,93,94] than fungal pellets [88,95]. Rheological aspects influence transport processes and consequently the effectiveness of the entire fermentation [89,96] as, for instance, oxygen delivery is impeded [94].…”
Section: (Techno)functional Properties and Use In Foodsmentioning
confidence: 99%